Effect of oregano and bay as natural preservatives in meat bread for extension of storage stability at ambient temperature. Issue 4 (5th February 2020) - Umaraw, Pramila; Chauhan, Geeta; Mendiratta, Sanjod Kumar; Verma, Akhilesh K.; Arya, Anita
Abstract: Natural herbs incorporated novel meat breads were studied for their shelf life analysis. Novel meat breads were formulated by fortifying whole wheat breads with protein (30% spent hen chicken meat), fiber (10% amaranth flour) and were flavored with culinary herbs, 0.5% oregano and 0.5% bay separately. These breads were stored at ambient temperature (27 ± 1 °C) for 9 days. Storage stability was analyzed in terms of various parameters such as pH, aw, oxidation parameters (PV, TBARS, free fatty acids, DPPH), microbiological estimation such as SPC, Coliforms, Yeast and mold count, Color analysis and sensorial profile. The outcome of present study was that the shelf life of novel protein and fiber fortified bread can be increased by incorporation of natural herbs viz. bay and oregano. Practical applications: Bread is a staple food item which is consumed worldwide and its consumption among snack food items ranks highest. Bread is cereal‐based snack product but deficient in good quality protein therefore addition of high quality animal protein would enhance its quality attributes, which is essential for healthy life. The practical implication of the study is that natural herbs (bay and oregano) can be efficiently used to enhance the quality and safety of novel meat breads stored at ambient temperature under aerobic packaging condition.